(untitled) (Research, Society and Development, 2021)
The incidence of facial trauma has been growing around the world due to several factors, including sports practice. Facial injuries can have catastrophic consequences for athletes, so it is extremely important to examine the rates, risk factors and nature of these traumas. The aim of this study was to investigate the incidence of facial trauma, such as the most affected anatomical regions and treatment through an integrative literature review. An integrative review was carried out, through research in the SCIELO, PUBMED and MEDLINE databases, using the Bolean operator AND, and inclusion criteria were articles in English that talk about the incidence of facial trauma in athletes, of professional category, as well as the anatomical regions involved, the sport and the use or not of facial and oral protection. The bibliographic surveys took place in March 2020. We analyzed 12 articles that met the inclusion criteria. The reviewed articles showed that the sport that most occurs facial traumas is soccer, the most affected anatomical region was the zygomatic complex, and the non-use of preventive measures was the main factor for the occurrence of traumas. This review revealed a high prevalence of maxillofacial lesions, with higher prevalence in the mandible region and zygomatic complex.